Freedom in Dependence: Reflections on the Conditions of a Christologically Grounded Anthropology - Hamilton, Nadine (Studies in Christian ethics, 2026)
This article reconceives Christian freedom as dependence. It diagnoses how modern Protestant semantics, despite relational rhetoric, tend to default to the autonomous subject. It retrieves Luther's paradox ?lord of all/servant of all? and reads Bonhoeffer's freedom as responsibility and vicarious representative action in his Ethics as a test case: a Christologically framed ethic that, because it requires judgment and decision, remains vulnerable to subject-centred recoding. Disability theology functions as a hermeneutical correction, relocating freedom within vulnerability, shared agency, and enabling relations. Dogmatically, in the unio hypostatica and communicatio idiomatum, the crucified-and-risen Christ's enduring wounds disclose divine freedom as shared self-commitment. Returning to Bonhoeffer, the article unfolds the imago Dei within an ?ontology of the Name?, proposing a Christologically grounded, relational anthropology. It finally asks whether the difficulty of thinking beyond autonomy reflects a tacit split between anthropology and soteriology, and explores how a Christological reorientation might reconfigure the field.